Linguocultural analysis of folklore texts - Sharipova Malikakhon Kahramon kizi, (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2026)
Linguoculturology, as an interdisciplinary field at the intersection of linguistics, cultural studies, and anthropology, provides a powerful framework for analyzing folklore texts as carriers of national worldview, collective memory, and cultural values. This paper conducts a comprehensive linguocultural analysis of selected Uzbek folklore texts, focusing on the heroic epic Alpomish, the Go‘ro‘g‘li cycle, traditional fairy tales such as Zumrad va Qimmat, and paremiological units (proverbs and sayings). Drawing on the systemic method of analysis, the study identifies key linguoculturomes — lexical, phraseological, and onomastic units that encode culturally specific concepts such as heroism (botirlik), hospitality (mehmondo‘stlik), family loyalty, and the cyclical nature of life. The research demonstrates that folklore texts serve not only as artistic expressions but also as repositories of the national linguistic picture of the world, reflecting the ethnos’s historical experience, moral norms, and cognitive models. Comparative insights with English folklore highlight both universal archetypes (triumph of good over evil, hero’s journey) and nationally specific features rooted in Central Asian nomadic traditions and Islamic-Turkic cultural layers. The findings underscore the relevance of linguocultural analysis for preserving intangible cultural heritage in the context of globalization and contribute to the development of Uzbek linguoculturology as a distinct scholarly direction.